Language Testing and Assessment - Shohamy, Elana; Or, Iair G.; May, Stephen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
In this third, fully revised edition, the 10 volume Encyclopedia of Language and Education offers the newest developments, including an entirely new volume of research and scholarly content, essential to the field of language teaching and learning in the age of globalization. In the selection of topics and contributors, the Encyclopedia reflects the depth of disciplinary knowledge, breadth of interdisciplinary perspective, and diversity of socio-geographic experience in the language and education field. Throughout, there is an inclusion of contributions from non-English speaking and non-western parts of the world, providing truly global coverage. Furthermore, the authors have sought to integrate these voices fully into the whole, rather than as special cases or international perspectives in separate sections. The Encyclopedia is a necessary reference set for every university and college library in the world that serves a faculty or school of education, as well as being highly relevant to the fields of applied and socio-linguistics. The publication of this work charts the further deepening and broadening of the field of language and education since the publication of the first edition of the Encyclopedia in 1997 and the second edition in 2008.
Assessing Language Domains -- Methods of Assessment -- Assessment in Education -- Assessment in Society.
Keywords: Language and education; Applied linguistics; Literacy; Educational policy; Education and state; Language Education; Applied Linguistics; Literacy; Educational Policy and Politics